General practitioners' self-reported competence in the management of sexual health issues - a web-based questionnaire study from Finland - Manninen Sanna-Mari; Kero Katja; Perkonoja Katariina; Vahlberg Tero; Polo-Kantola Päivi (TAYLOR & FRANCIS LTD, 2022)
Objective Although sexual problems are common, they are rarely brought up in appointments with general practitioners (GPs). We aimed to assess the barriers that hinder GPs from bringing up sexual health issues and to evaluate the need for education on sexual medicine. Design A web-based questionnaire was used. Setting Four fields were included: A) the self-reported competence in discussing sexual health and treating patients with these issues, B) the barriers to bringing up patients' sexual health problems, C) the source of education on sexual medicine and D) the need for education on sexual medicine. Subjects A random sample of 1000 GPs in Finland (a response rate of 43.5%, n = 402). Main outcome measures GPs' self-assessed competence in discussing and treating sexual health issues, related barriers to bringing up the topic and the reported need for education. Results The main reasons reported for not bringing up sexual health issues were shortness of the appointment time (85.6%), a lack of knowledge (83.6%) and a lack of experience with sexual medicine (81.8%). The male GPs reported better competence in discussing the issues and treating male patients, whereas the female GPs reported better competence in discussing the issues with female patients. No differences emerged between genders regarding treating female patients. Nearly 90% of the GPs expressed needing more education about sexual medicine. Conclusions Although the GPs reported good competence in discussing sexual health issues with their patients, several barriers to bringing up sexual health issues emerged. Continuing education was desired and could lessen these barriers.